عصر حاضر میں تربیت اولاد میں افراط و تفریط اور حدیث نبوی کا تقابلی جائزہ: An Analytical Comparison of Extremism and Negligence in Contemporary Child Rearing with Prophetic Hadith (Al-Aasar, 2025)
Parenting in the modern era is a complex and challenging responsibility, often marked by extremes of permissiveness and strictness. These imbalances in parenting styles can lead to negative outcomes for children, such as behavioral issues, emotional instability, and a lack of moral grounding. This research article aims to explore the challenges of contemporary parenting and compare them with the teachings of the Prophet Muhammad (peace be upon him) as documented in Hadith literature. The study highlights the importance of moderation and balance in parenting, as emphasized in Islamic teachings. It examines the consequences of both permissive and authoritarian parenting styles and contrasts them with the Prophetic model, which advocates for compassion, discipline, and moral education. The article also provides practical recommendations for parents to adopt a balanced approach rooted in the teachings of the Prophet (peace be upon him). By analyzing modern parenting practices in light of Hadith, this research underscores the timeless relevance of the Prophetic model in addressing contemporary challenges. It concludes that a balanced approach to parenting, guided by Islamic principles, can lead to the holistic development of children, preparing them to become responsible and morally upright individuals.